IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK (KIP) DI KABUPATEN KEPULAUAN MERANTI TAHUN 2011-2015 - Herda Astuti; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research have to know about Implementation of Openess Public Information ( OPI) in Meranti Islands Regency. As for the background of this research is still so many Society although Caretaker Public Organization didn’t know and understand purpose of the birth of The Law Openess Public Information (OPI) so for some people who need the information from public bodies have difficulty obtaining Public Information for Various reason. This research applied the Theory of Implementation, so the methode used is the research methode with a qulitative approach. The data obtained by the interview and documentation data analyze for analyze with Descriptive analyze methode.This research shows that related to the role of the public relations of the Meranti District Secetariat as the Information and Documentation managing officials in the government of Meranti Islands, basically has been going on according to the provision that has been mandated in the constitution No 14 Year 2008 about the Opennes of Public Of Information. Even it there are several obsticles during the implementation that is related to fascilities and budget but everything still goes on according to the expectations. This is also supported by the releasing of the rule by the head of district of Meranti Islands No 21 Year 2012 about the guidelines of working information and documentation at The Environment of Meranti Island Government so the workflow and rsponsibility becomes clear.Keywords : Implementation, Public Information.